Evaluation of the holistic health care program to develop the capacity of prison public health volunteer leaders (PPHVs) in Thailand: A participatory action research - Phannathat Tanthanapanyakorn; Sasiwimol Chanmalee; Sootthikarn Mungkhunthod; Chaninan Praserttai; Nonlapan Khantikulanon (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: Health promotion in correctional settings faces challenges due to limited healthcare access and restricted environments. Nurses are primary healthcare providers in correctional institutions; however, evidence on nurse-led capacity-building programs for inmate health volunteers remains limited. Developing the capacity of Prison Public Health Volunteer Leaders (PPHVs) through a holistic healthcare approach can enhance their self-reliance. Objective: This study aimed to collaboratively develop, implement, and evaluate a holistic health care program to strengthen the capacity of PPHVs at the Central Correctional Institution for Young Offenders in Pathum Thani Province, Thailand. Methods: This study employed a Participatory Action Research (PAR) design. A total of 100 well-behaved inmates were purposively selected as PPHVs and actively engaged as co-participants throughout the PAR process. The intervention was collaboratively designed and implemented over five weeks, comprising ten participatory training sessions that addressed physical, mental, social, and environmental health dimensions. Quantitative data were collected using validated questionnaires assessing knowledge, attitudes, health practice skills, data management skills, and overall capacity at baseline, post-intervention, and at 1-month follow-up. Data were analyzed using repeated measures analysis of variance (ANOVA). Results: The findings revealed statistically significant improvements (p <0.001) in participants’ knowledge (F = 778.41, ηp² = 0.887), attitudes (F = 889.09, ηp² = 0.900), health practice skills (F = 1241.89, ηp² = 0.917), data management skills (F = 546.81, ηp² = 0.847), and overall capacity (F = 727.48, ηp² = 0.880). These outcomes indicate substantial enhancement in PPHVs’ ability to perform health promotion and data management roles proficiently. Conclusion: The holistic health care program significantly improved PPHVs’ capacity, suggesting promise for strengthening inmate health volunteer programs in correctional settings. These findings have significant implications for nursing practice in designing capacity-building programs, nursing education in preparing nurses for correctional care, and nursing policy in developing standards for correctional nursing in Thailand. Trial Registry Number: Thai Clinical Trials Registry (TCTR20260115003)